Sliding mode control with enhanced error-dependent observer switching mechanism for piezoelectric linear motor - Zhang, Chen; Zhou, Miaolei; Shao, Xingling; Geng, Xiangyu; Zhang, Xiuyu (Nonlinear dynamics, 2025)
This study investigates the problem of nano-scale precision trajectory tracking control with extended state observer (ESO) for piezoelectric linear motors (PELMs). Since PELMs need different driven signals for various operating requirements, they are subject to different degrees of system uncertainties and external disturbances. By analyzing the input–output characteristics of the PELM, the system model for the PELM is constructed. Due to the high uncertainties of the PELM, an ESO is introduced for the estimation of disturbances. Specifically, an enhanced error-dependent observer switching mechanism (EOSM) is established based on the disturbance features. Then, to suppress the adverse effects of disturbances, an EOSM based super-twisting sliding mode control (EOSM-STSMC) scheme is developed. The proposed control strategy can implement disturbance estimation and uncertainty inhibition, thus the complex nonlinearities of the PELM can be delicately treated and high accuracy tracking effect can be achieved. The system stability analysis is provided with the aid of the Lyapnuov function. Finally, a plenty of experiments are implemented on the PELM for tracking point-to-point trajectory, sinusoidal signal, and third-order S-curve. The proposed controller has smaller performance index values compared to the traditional SMC method, linear ESO based SMC method, and nonlinear ESO based SMC method. Experimental results indicate that the proposed controller has satisfactory transient and steady state tracking performance.